(untitled) (Fiep Bulletin - online, 2011)
The research was planned and carried out based on the badminton sport that, since its establishment in India over 200 years ago, which is practiced individually or in pairs, and being a dynamic sport, agile and quick, it has grown and fascinated people, leading to a significant increase of practitioners in Minas Gerais in Brazil and worldwide. The research aimed to verify by Semo agility test (Johnson & Nelson, 1979, Apud Marins & Giannichi, 2008.) a possible improvement in the level of agility in students practicing the badminton. The tests were applied during the interclass sports championship at Corina Ferraz de Brito School, the months of September and October of 2010 in Almenara, a town in Minas Gerais. Six 13-to-14-year students, duly authorized by their parents, participated in the research. The agility tests were applied and measured at three different times during the competition. It has seen in the competition a decline or decrease of time around "2 ½ seconds" of difference between the tests used at baseline (September) compared to the last (October). It is concluded that the Semo test applied in 13-to14-year students practicing badminton, showed levels of improvement in agility (based on time) and the effective development of physical fitness as a result of practice and participation in competitions imposed during a period of two months.